2007
DOI: 10.1007/s11469-007-9065-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Dimensions of Spirituality in Chemical Dependence Treatment and Recovery: Research and Practice

Abstract: Spirituality and religiousness have long been associated with physical and mental health. The scientific treatment of religiosity as a multi-dimensional phenomenon is well established, especially in relation to chemical dependence treatment. Indeed, over 100 instruments are available for measuring various dimensions of religiosity. The more recent emergence of spirituality as an accepted construct in research has seen the development of a growing number of instruments to measure aspects of spirituality. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…The DSES currently forms part of an ongoing study of adolescent alcohol abuse and helping behaviors. Shorkey and Uebel reviewed 10 measures for use in addiction research, and concluded regarding the DSES that "the usefulness of this scale for assessing the spiritual experience of a person in treatment and recovery may be profound" [61].…”
Section: Dses and Addictionsmentioning
confidence: 99%
“…The DSES currently forms part of an ongoing study of adolescent alcohol abuse and helping behaviors. Shorkey and Uebel reviewed 10 measures for use in addiction research, and concluded regarding the DSES that "the usefulness of this scale for assessing the spiritual experience of a person in treatment and recovery may be profound" [61].…”
Section: Dses and Addictionsmentioning
confidence: 99%
“…These are important information gaps that must be addressed to improve the assessment of spirituality within health care. 13 Several authors have tried to develop a catalogue of instruments to assess spirituality, [14][15][16][17][18] but these reviews were not systematic, limited to specific populations, and essentially provided only descriptive information. To-date, no systematic review has been performed to catalogue and classify available instruments to assess spirituality within clinical health care research.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the scales briefly mentioned here, a variety of other available measures of spirituality are available in the literature on AOD dependence recovery (see Morgan, 2002;Neff, 2008;Shorkey, Uebel, & Windsor, 2008;Stanard, Shandhu, & Painter, 2000). Shorkey et al (2008), considering how the more recent emergence of spirituality as an accepted construct in research contributed to the development of a growing number of instruments to measure aspects of spirituality, selected 10 spirituality scales for review and discussion. The authors conceptualize the scales in terms of their aggregate and overlapping usefulness for research and practice, outlining the salient dimensions of spirituality measured by each scale.…”
Section: Measuring Spirituality In Recoverymentioning
confidence: 99%
“…It is notable that the spirituality scales included in the review by Shorkey et al (2008) were largely generic; that is, they assessed spirituality from a more holistic, nondenominational perspective. One scale discussed by the authors was developed to measure spiritual maturity from a Christian New Testament perspective informed by object relations theory (Spiritual Assessment Inventory [SAI]; Hall & Edwards, 1996, 2002.…”
Section: Measuring Spirituality In Recoverymentioning
confidence: 99%